PERILAKU HIDUP BERSIH DAN SEHAT PADA KELUARGA DI KELURAHAN SUKARAMAI KECAMATAN PEKANBARU KOTA KOTA PEKANBARU - Situmeang, Fitri; Marnelly, T. Romy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was aims to determine the extent of the Implementation of Clean and Healthy Living (PHBS) in families in RW 07, Sukaramai Sub-District, Pekanbaru City District. The design of this research is in the form of Quantitative Descriptive with sample selection using the Census Technique which is to take all objects in accordance with predetermined criteria. Data collection techniques used were questionnaire sheets, documentation, and direct observation. The analysis used is descriptive quantitative analysis which is presented in tabular form and then explained in detail. The results of this study are respondents have a high level of knowledge and response or attitude, however the implementation of PHBS is not comprehensive and can be done well. Based on the level of PHBS implementation in families in RW 07, Sukaramai Village, as many as 37 households are in the Main Health Level category by achieving an assessment score between 40-49 or around 66% by occupying the green line scale, which means achieving PHBS in families in RW 07 Sukaramai Village is already above the national standard. The factors that inhibit PHBS are poor water quality, interference with breast milk, not available healthy latrines, there are still many household members who smoke, and so forth. Based on the results of this study it is suggested to the community to further improve Clean and Healthy Behavior in the family in accordance with the principles of health. Keywords: PHBS, Infrastructure Facilities, Family.